Increasing Accessibility to Science in Early Childhood Teacher Education Through Collaboration Between Teacher Educators and Science/Engineering Academics - Howitt, Christine; Blake, Elaine; Calais, Martina; Carnellor, Yvonne; Frid, Sandra; Lewis, Simon; Mocerino, Mauro; Parker, Lesley; Sparrow, Len; Ward, Jo; Zadnik, Marjan (Springer, 2012)
Various reports have identifi ed urgent needs for science education in Australia, in particular, in relation to maintaining and increasing capability to teach science at all levels of schooling (e.g. Australian Academy of Technological Sciences and Engineering 2002 ; Goodrum et al. 2001 ; Tytler 2007 ) . The most recent reports at both the national and state levels have recommended the development of comprehensive ‘action plans’. For example, the Commonwealth sponsored the initial phase of production of a National Action Plan for Australian School Science Education 2008–2012 (Goodrum and Rennie 2007 ) . Many of these reports highlight a ‘crisis’ in science education, in terms of students’, teachers’ and national needs. Briefly, they provided convincing evidence that students are not enrolling in science courses or science education courses in suffi cient numbers; appropriately trained teachers of science, technology, engineering and mathematics (STEM) knowledge, skills and/or appreciation continues to be a national concern, especially in innovation and economic terms.Over the past decade, a number of initiatives have attempted to address the student- related dimensions of this problem, particularly increasing engagement in STEM at the upper primary and secondary school levels. Examples of these include the Australian Academy of Science ‘Primary Connections’ programme, the Collaborative Australian Secondary Science Programme (CASSP), the Creativity in Science and Technology (CREST) programme, the Science Education AssessmentResources (SEAR) programme, the Australian Science Teachers’ Association Science Awareness Raising Model and the recent Scientists in Schools (SiS) programme. However, few of the initiatives to date have focused specifically on the needs of pre-service teachers, and even fewer have addressed the needs of early childhood pre-service teachers.This chapter re ports on the outcomes of a project that took a highly collaborative and cross-discipline approach among teacher educators, science/ engineering academics and early childhood pre-service teachers to encourage the latter to teach more science, with greater confi dence, in the classroom. This collaborative approach involved both the development and delivery of science modules within a science methods course. For the purposes of this research, early childhood was defi ned aschildren between the ages of 3 and 8 years. The fi rst part of this chapter describes the literature in relation to three relevant areas of research. First, the characteristics of early childhood pre-service teachers are described in relation to science. Second, various approaches used to improve pre-service teachers’ confi dence and competence to teach science are discussed. Third, an overview of collaboration between scientists and teachers is presented. In the remainder of the chapter, the projectdesign and fi ndings are discussed.